The role of attention in human motor resonance. - Guglielmo Puglisi; Antonella Leonetti; Ayelet Landau; Luca Fornia; Gabriella Cerri; Paola Borroni (PLoS ONE)
Observation of others' actions evokes in primary motor cortex and spinal circuits of observers a subliminal motor resonance response, which reflects the motor program encoding observed actions. We investigated the role of attention in human motor resonance with four experimental conditions, explored in different subject groups: in the first explicit condition, subjects were asked to observe a rhythmic hand flexion-extension movement performed live in front of them. In two other conditions subjects had to monitor the activity of a LED light mounted on the oscillating hand. The hand was clearly visible but it was not the focus of subjects' attention: in the semi-implicit condition hand movement was relevant to task completion, while in the implicit condition it was irrelevant. In a fourth, baseline, condition subjects observed the rhythmic oscillation of a metal platform. Motor resonance was measured with the H-reflex technique as the excitability modulation of cortico-spinal motorneurons driving a hand flexor muscle. As expected, a normal resonant response developed in the explicit condition, and no resonant response in the baseline condition. Resonant responses also developed in both semi-implicit and implicit conditions and, surprisingly, were not different from each other, indicating that viewing an action is, per se, a powerful stimulus for the action observation network, even when it is not the primary focus of subjects' attention and even when irrelevant to the task. However, the amplitude of these responses was much reduced compared to the explicit condition, and the phase-lock between the time courses of observed movement and resonant motor program was lost. In conclusion, different parameters of the response were differently affected by subtraction of attentional resources with respect to the explicit condition: time course and muscle selection were preserved while the activation of motor circuits resulted in much reduced amplitude and lost its kinematic specificity.